The history of American literature on film - Leitch, Thomas M., 1951- (New York : Bloomsbury Academic, 2019)
This book responds to a growing academic interest in theorizing care and care work in the early childhood education and care (ECEC) sector. The contributors theorize a new feminist ethics of care in everyday early childhood practice, revealing its complexities and importance. Drawing on feminist theories and philosophies, the chapter authors show how the caring practices of early childhood educators involve values, emotions, decision-making, action and work. Using cutting-edge theory, authors address the social locations and the inclusion and exclusion of both care givers and care receivers. With contributions from Belgium, Canada, New Zealand, the UK and the USA, the volume brings together early childhood studies, sociology, psychology, philosophy and critical disability studies to offer diverse perspectives on feminist ethics of care in early childhood practice and its possibilities and dangers.
1, Introduction: American cinema and American literatures -- 2, 1895-1915: The attraction of adaptation -- 3, 1915-27: American exotics -- 4, 1927-39: Novel impressions -- 5, 1939-51: Invisible adaptation -- 6, 1951-67: Weaponized best sellers -- 7, 1967-75: Counterculture classics -- 8, 1975-89: Screening the silenced -- 9, 1989-2007: Adapt or die -- 10, 2007-18: Entertainment for me
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: 20.-21. století; americká literatura; dějiny filmu -- Spojené státy americké -- 20.-21. století; film a literatura -- Spojené státy americké; filmové adaptace -- Spojené státy americké -- 20.-21. století; filmy -- Spojené státy americké -- 20.-21. století; American literature; history of film -- United States -- 20th-21st centuries; film and literature -- United States; film adaptations -- United States -- 20th-21st centuries; films -- United States -- 20th-21st centuries; Hollywood (Los Angeles, Kalifornie); Hollywood (Los Angeles, California); e-knihy online; monografie; e-books online; monographs